Perlindungan Hukum Terhadap Pemilik Hak Atas Tanah Bersertifikat Dalam Pelaksanaan Pengembangan Jalan Usaha Tani (Studi Kasus : Di Desa Kalijaga Tengah Kecamatan Aikmel) - Suhael, Suhael (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2024)
The concept of a welfare state involves the active pursuit of citizen welfare, including the implementation of road infrastructure development. However, in its execution, the state is obligated to protect human rights, such as citizens' land ownership rights. Hence, it is impermissible to engage in arbitrary practices regarding community land rights, including the implementation of Agricultural Road Development (farm road) in Kalijaga Tengah Village, Aikmel District. The issue addressed in this research pertains to the legal mechanism of implementing farm road in positive law and the legal protection afforded to certified landowners during the execution of farm road in Kalijaga Tengah. This study adopts a normative-empirical research approach, utilizing methods such as the statute approach, conceptual approach,and case approach. The findings indicate that the legal mechanism for implementing farm road is regulated in the Directorate General of Infrastructure and Agricultural Facilities' decree on Technical Guidelines for Agricultural Land Conservation and Rehabilitation in 2021. However, the unprocedural actions of the Village Head and committee have weakened the legal protection of the physical data of land certificate owners, potentially leading to legal issues regarding the validity of this physical of land certificate owners data in the future.